Toward sustainable coffee production in Vietnam: more coffee with less water - Amarasinghe, Upali A.; Hoanh, Chu Thai; D'Haeze, Dave; Hung, T.Q. (Elsevier, 2015)
Inefficient use of irrigation water threatens coffee production in Vietnam, the second largest producer worldwide after Brazil. This paper examines the irrigation issues that constrain sustainable coffee production in Vietnam. The period from January to April is a crucial time in the growth of the coffee crop. It requires irrigation, because rainfall only provides 25% of the potential crop evapotranspiration demand. According to crop phenology, this period also requires induced water stress, because it coincides with breaking the dormancy of flower buds and initiation of cherry development, which is crucial for achieving high yield. This paper proposes an irrigation supply of 120 or 150 mm between January and April in a year preceded by good or average rainfall respectively, in November and December. This is equivalent to 364 or 456 liters/plant/round in 3 rounds/year, which is only 70% of the locally recommended level by the Ministry of Agriculture and Rural Development. Synchronizing this irrigation supply with the management of other inputs could increase average yield up to 4000 kg/ha, from the present level of 2400 kg/ ha making coffee production both sustainable and economically viable. In order to achieve this, building capacity of farmers to follow the irrigation and input application schedules is crucial.